Three decades of the Malaysian common market : Appraisal, overview and future directions / Wee Chong Hui … [et al.] - Wee, Chong Hui; Amin, Nicholas (1999)
Malaysia is trade dependent. It has been enjoying trade surpluses since 1963. However, its terms of trade has been deteriorating from the seventies. Malaysia's dynamic manufacturing sector has contributed the bulk of export earnings. Nonetheless, the manufacturing sector is narrow-based and Malaysia is over-dependent on the electrical and electronic sub-sector. Malaysia imports of capital and intermediate goods are also substantial, resulting in low value addition. Tariff protection has encouraged import substituting industries. Nevertheless, consumers mers have borne higher prices of protected products. The heavy industries may require restructuring in order to increase competitiveness, particularly with the abolition of tariffs under WTO agreements.